Analisis Peran Public Relation Dalam Peningkatan Brand Image Perusahaan Di Bank Sumatera Selatan Bangka Belitung - Sari, Wulan Citra; Prihatini, Lishapsari; Mardianto, Mardianto (@-Publik: Jurnal Administrasi Publik, 2023)
The important role of Public Relations in a company is to create and maintain a positive image in the eyes of the public. In an effort to build and maintain a positive company image, companies can utilize social media to communicate with the public quickly and effectively, enabling two-way communication between Public Relations and the wider community. Apart from that, social media is also used to evaluate a company's brand image. However, in the context of this research, there are several problems that need to be addressed. One of them is the lack of human resource support in the Public Relations team at Bank Sumatra Selatan Bangka Belitung. Apart from that, the unequal level of education of the community or customers can make it difficult to understand the information conveyed by Public Relations, especially for those who have a lower level of education. This could be the cause of complaints later on. This research aims to analyze the role of Public Relations in improving the company's brand image at Bank Sumatra Selatan Bangka Belitung. The data analysis technique used is qualitative data analysis. The research results show that, overall, Public Relations has played a good role in efforts to improve the company image at Bank Sumatra Selatan Bangka Belitung, although there are still several obstacles, such as a lack of human resource support in the Public Relations team and unequal levels of community/customer education. makes it difficult to understand the information conveyed, which in the end can result in complaints at a later date.